2017
DOI: 10.1007/s11356-017-9810-y
|View full text |Cite
|
Sign up to set email alerts
|

Biology and management of Avena fatua and Avena ludoviciana: two noxious weed species of agro-ecosystems

Abstract: Avena fatua and Avena ludoviciana are closely related grass weed species infesting a large number of crops around the world. These species are widely distributed in diverse agro-ecosystems from temperate to sub-tropical regions due to their unique seed traits, successful germination ecology, high competitive ability, and allelopathic potential. A. fatua is more widespread, adaptable, and problematic than A. ludoviciana. Both these species infest major winter and spring crops, including wheat, oat, barley, cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 120 publications
1
19
0
Order By: Relevance
“…Field pea is a very poor competitor against weeds compared to other crops due to its weak early vigour at the seedling stage [ 8 , 9 ]. Globally, herbicides are widely used for weed control during pea cultivation, and although instantly effective, overuse of herbicides with similar active ingredients and modes of action is resulting in herbicide resistant weed biotypes [ 10 ] and increased production costs [ 11 ]. Herbicides can also potentially affect rhizobium and symbiotic nitrogen fixation with field pea, causing smaller positive impacts on subsequent crop rotations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Field pea is a very poor competitor against weeds compared to other crops due to its weak early vigour at the seedling stage [ 8 , 9 ]. Globally, herbicides are widely used for weed control during pea cultivation, and although instantly effective, overuse of herbicides with similar active ingredients and modes of action is resulting in herbicide resistant weed biotypes [ 10 ] and increased production costs [ 11 ]. Herbicides can also potentially affect rhizobium and symbiotic nitrogen fixation with field pea, causing smaller positive impacts on subsequent crop rotations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Avena fatua infests wheat (Triticum aestivum L.) crops in the mountainous areas of northern Spain where winters are cold, while A. sterilis is more abundant in the warm central and southern regions of the Iberian Peninsula (Fernández-Quintanilla et al 1997;García Baudín 1982). These tall grasses are considered especially worrisome due to their strong competitive ability, reducing cereal crop yields between 10% and 60% (Bajwa et al 2017;Fernández-Quintanilla et al 1997). This success of A. sterilis as a weedy species is explained, in part, by its high seed production, earlier shedding of seeds (Barroso et al 2006), and the capacity of its seeds to remain dormant in the seedbank for several years (Bajwa et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is a wild oat that is widespread all over the world, growing in various climatic zones from the tropics to the polar circle. A. fatua is considered to be one of the worst annual weeds in temperate zone cereals [ 28 , 29 ], causing enormous problems in agriculture [ 30 , 31 , 32 , 33 ]. Loskutov and Rines [ 1 ] have concluded that this species is a source of resistance to various oat diseases.…”
Section: Introductionmentioning
confidence: 99%